Analisis Prinsip Demokrasi Dalam Konstitusi Indonesia: Tinjauan Terhadap Implementasi dan Tantangannya - Izwah Marhamah; Anis Sri Wijayanti; Martika Suci Ristyawati; Sella Agri Bardana; Dian Permata Sari (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
This article discusses the principles of democracy in the 1945 Constitution of Indonesia as the foundation of the country's governance system. Democracy, emphasizing popular sovereignty, freedom, equality, and public participation, is enshrined in various articles of the Constitution, such as Article 1(2), Article 22E, and Article 28. This article analyzes how these principles are implemented in practice through mechanisms such as elections, public participation, and freedom of expression. However, the implementation of democracy in Indonesia faces various challenges, including money politics, identity politicization, social inequality, and weak law enforcement. Using a descriptive-analytical approach to secondary data, the article finds that while democracy has a solid constitutional foundation, these challenges hinder its quality. The article recommends regulatory strengthening, enhanced political education, and eradication of corruption practices to support a more inclusive and representative democracy.